Anti-adipogenic effect of sage (Salvia officinalis L.) hot-water extract on 3T3-L1 adipocyte and HepG2 hepatocyte - Ji-Yun Bae; Sung-Sil Hong; Mi-Ja Kim (Journal of Functional Foods)
Sage was extracted to hot water (S-HW) to evaluate its anti-adipogenic effect in 3 T3-L1 adipocytes and oleic acid-induced HepG2 hepatocytes. The accumulation of fat in 3 T3-L1 adipocyte and HepG2 hepatocyte was reduced by 95 and 32 %, respectively, at 100 μg/mL compared to control. The expression of adipocyte marker genes (pparγ, c/ebp-α, srebp-1c, ap2, fas, scd1, acc1, and cd36) in 3 T3-L1 adipocytes decreased significantly compared to adipocytes when treated with 100 μg/mL of S-HW (P < 0.05). Similarly, the expression of adipocytes marker genes in HepG2 hepatocyte was significantly reduced at 50 μg/mL of S-HW compared to positive control (P < 0.05). The expression of adipocyte marker proteins also decreased when 3 T3-L1 adipocyte and HepG2 hepatocyte were treated with S-HW. Therefore, S-HW has confirmed anti-adipogenic effect through the regulation of genes involved in fat accumulation in 3 T3-L1 adipocyte and HepG2 hepatocyte.